Strategi Evaluasi Kinerja Guru Sebagai Upaya Peningkatan Kualitas Pendidikan di Sekolah Dasar - Rizka Zahara; Rosa Rahmadani; Saripa Aini (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Teacher performance evaluation is essential to determine their competence in teaching and support professional development. Teacher productivity is a key factor in creating an effective educational environment, with a focus on individual and organizational dimensions. This literature review aims to analyze various approaches to teacher performance evaluation that have been reviewed in the latest literature. This study uses a literature review method, which is the process of searching and analyzing various sources of information, such as journals, books, and other published manuscripts, related to the research topic. From the results of this study, it can be concluded that teacher performance evaluation has a very important role in improving the quality of education, especially at the elementary school level. Evaluations that are carried out periodically and are evidence-based, using a comprehensive and adaptive approach, have proven effective in identifying the strengths and weaknesses of teacher performance, and providing a clear basis for their professional development. The competency-based evaluation model provides great benefits in improving the quality of teaching by assessing four main aspects of teacher competence, namely pedagogical, personality, social, and professional.